2018
DOI: 10.1111/jsr.12747
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive performance in insomnia disorder: The impact of hyperarousal and short sleep duration

Abstract: Given the recent evidence on the association between hyperarousal in insomnia disorder and neurocognitive deficits, we aimed to examine the effect of short sleep duration on neurocognitive reaction time tests in insomnia disorder sufferers. We recruited subjects with insomnia disorder (n = 35, mean age = 40.6 years) who scored ≥29 on a Hyperarousal Scale, and a group of controls (n = 54, mean age = 31.5 years) who had no sleep disorders and scored <26 on the Hyperarousal Scale. Participants completed two in-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 38 publications
5
39
0
Order By: Relevance
“…Short sleep duration was associated with a higher risk of students reporting failed examinations in the present study. This finding was independent of a range of lifestyle factors and psychological distress, and the results are in line with previous field and laboratory studies [13,17,18,37,38]. The relationship between sleep duration and failed examinations was further elucidated in some additional regression analyses that were conducted, where we distinguished between six categories of sleep duration.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Short sleep duration was associated with a higher risk of students reporting failed examinations in the present study. This finding was independent of a range of lifestyle factors and psychological distress, and the results are in line with previous field and laboratory studies [13,17,18,37,38]. The relationship between sleep duration and failed examinations was further elucidated in some additional regression analyses that were conducted, where we distinguished between six categories of sleep duration.…”
Section: Discussionsupporting
confidence: 89%
“…For example, a meta-analysis showed that insomnia was associated with mild to moderate impairments on more complex cognitive functioning, such as working memory and executive control, whereas performance on areas such as alertness, sustained attention and vigilance were not affected compared to normal sleepers [34]. Recent advancements in this field suggest that these impairments might be more pronounced among those who have the subtype of insomnia characterized by short sleep duration [17,18]. Indeed, our findings indicate that those with insomnia and a short sleep duration (<6 h) had the highest risk of reporting more failed exams relative to the other categories when no other variables were controlled for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prediction that TST would be associated with performance on tests measuring higher‐order cognitive functions was generally supported, but the type of cognitive task was important. For the reasoning and working memory tasks, associations between longer sleep duration and better performance agree with the direction of association reported in prior studies examining self‐reported TST in adults without ICDs (Fernandez‐Mendoza et al., ; Khassawneh et al., ). This suggests that patients with ICDs may receive cognitive benefits following increased sleep duration.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, self‐reported TST (i.e. <6 hr) has been associated with worse performance on tests measuring higher‐order or executive function in younger adults with insomnia (Khassawneh, Bathgate, Tsai, & Edinger, ), processing speed and executive function in middle‐aged adults with insomnia (Fernandez‐Mendoza et al., ), and worse global cognitive performance in older adults (Lo, Loh, Zheng, Sim, & Chee, ). Other research has found that objectively measured (i.e.…”
Section: Introductionmentioning
confidence: 99%